Metal contamination in soil and vegetables around Savar tannery area, Dhaka, Bangladesh: A preliminary study for risk assessment - Al Mizan; Mohammad Arif Hasan Mamun; Md Saiful Islam (Heliyon, 2023)
Monitoring of heavy metal concentrations in soil and their accumulation in vegetables grown in the newly shifted tannery area of Savar, Bangladesh, is crucial for human health. Heavy metals (i.e., Cr, Pb, Cu, Zn, Ni, and Cd) concentrations in soil and vegetable samples were determined by atomic absorption spectrophotometer (AAS). In soil, 3220 mg/kg Cr was observed, which was 32-fold greater than the WHO/FAO recommended limit. Ecological risk indices such as the contamination factor, enrichment factor, pollution load index, and geoaccumulation index showed metal levels as moderately to very highly contaminated. The non-carcinogenic risk (NCR) was found to be higher, and the carcinogenic risk (CR) exceeded the acceptable value 1 × 10−6 and posed greater risks to children than adults, especially for Cr in soil. The main exposure pathway for soil metals was 97.8–99.9% due to oral ingestion. The concentration of heavy metals especially Cr, Pb, Zn, and Cd, in vegetables was alarming as they crossed the safety limit. The calculated mean hazard index (8.71) for vegetable samples showed elevated levels of potential NCR, while CR for Cr and Cd, exceeded the acceptable limit of 1 × 10−6, indicating the probability of cancer risk to humans through the consumption of vegetables. This study revealed a to-and-fro analysis of the present scenario of the tannery area, giving importance to human health and the environment.